Invasion Activities and Karabakh Events - Alizade, Rövşen (Fırat University, 2013)
As the Tzardom invaded North Azerbaijan territories, they also executed policies of Armenization of population in order to settle continuously on this territory. After Türkmen Çay treaty signed between Russia and Iran in 1828, this situation became continuous and deliberate. Immigration of Armenians from Iran to North Azerbaijan was confirmed with article no. 15 of the same treaty. With Edirne Treaty signed in 1829 the process of Armenian immigration from Ottoman Empire to recently invaded North Azerbaijan began. One of the immigration directions of Armenians was Karabağ territory. With this treaty 84.000 Armenians immigrated towards Karabağ and its vicinity. With regard to official information we can say that 18.000 Armenians emigrated from Iran to Karabağ between 1828 and 1830, 50.000 Armenians emigrated after 1828 and 84.000 Armenians emigrated from Ottoman Empire

Çarlık devri Kuzey Azerbaycan topraklarını işgal ettikçe, bu topaklarda sürekli oturmak için nüfusun Ermenileştirme siyasetini de yürütmekteydi. 1828 yılı Rusya ile İran arasında yapılan Türkmen Çay antlaşmasından sonra bu durum daha sürekli ve maksatlı şekil aldı. Ermenilerin İran’dan Kuzey Azerbaycan’a göç ettirilmesi aynı antlaşmanın 15. maddesi ile tasdik edilmekteydi. 1829 yılında Edirne antlaşması ile Osmanlı İmparatorluğundan da Ermenilerin yeni işgal edilmiş Kuzey Azerbaycan topraklarına göç ettirilmesi süreci başlamıştır. Ermenilerin göç istikametlerinden biri Karabağ arazisiydi. Bu antlaşma ile 84.000 ermeni Karabağ ve etrafına göç ettirilmiştir. Resmi bilgilere dayanarak söyleye biliriz ki, 1828-1830 yılları arasında Karabağ’a İran’dan 18.000, 1828’den sonra 50.000, Osmanlı İmparatorluğundan ise 84.000 ermeni göçü gelerek yerleşmiştir
İşgalcilik Faaliyetleri ve Karabağ Olayları